Omics insights into extracellular vesicles in embryo implantation and their therapeutic utility. Issue 6 (10th January 2023) - Poh, Qi Hui; Rai, Alin; Salamonsen, Lois A.; Greening, David W.
Abstract: Implantation success relies on intricate interplay between the developing embryo and the maternal endometrium. Extracellular vesicles (EVs) represent an important player of this intercellular signalling through delivery of functional cargo (proteins and RNAs) that reprogram the target cells protein and RNA landscape. Functionally, the signalling reciprocity of endometrial and embryo EVs regulates the site of implantation, preimplantation embryo development and hatching, antioxidative activity, embryo attachment, trophoblast invasion, arterial remodelling, and immune tolerance. Omics technologies including mass spectrometry have been instrumental in dissecting EV cargo that regulate these processes as well as molecular changes in embryo and endometrium to facilitate implantation. This has also led to discovery of potential cargo in EVs in human uterine fluid (UF) and embryo spent media (ESM) of diagnostic and therapeutic value in implantation success, fertility, and pregnancy outcome. This review discusses the contribution of EVs in functional hallmarks of embryo implantation, and how the integration of various omics technologies is enabling design of EV‐based diagnostic and therapeutic platforms in reproductive medicine.